From Spatial to Social Asymmetry: Spontaneous and Conditioned Associations of Gender and Space. (March 2017) - Suitner, Caterina; Maass, Anne; Ronconi, Lucia
According to the spatial agency bias model, in Western cultures agentic targets are envisaged as facing and acting rightward, in line with writing direction. In four studies of Italian participants, we examined the symbolic association between agency and the rightward direction (Study 1, N = 96), its spontaneous activation when attributing agency to female and male targets (Study 2, N = 80) or when judging the authenticity of photographs of men and women (Study 3, N = 57), and its possible relation to stereotype endorsement (Study 4, N = 80). In Study 4, we used a conditioning paradigm in which participants learned a counterstereotypical new association; we developed a novel measure to assess the association between gender and spatial direction, namely, the spatial association task. Participants envisaged and cognitively processed male and female targets in line with the spatial agency bias model and reported lower benevolent sexism after learning a new counterstereotypical spatial association. Our findings raise awareness about the biased use of space (and its consequences) in the representation of women and men, so that all people, and especially communicators and policy makers, can actively intervene to promote gender equality. Additional online materials for this article are available to PWQ subscribers on PWQ's website athttp://journals.sagepub.com/doi/suppl/10.1177/0361684316676045